The local hormonal environment of tumor and perifocal zone in patients with breast cancer: data and prospects of their application - Yu. S. Shatova; E. M. Frantsiyants; I. A. Novikova; L. N. Vashchenko; V. A. Bandovkina; M. I. Vereskunova; A. N. Khugaeva; V. V. Tokmakov (ABV-press, 2016)
The expression of androgen receptors is maximal in the luminal subtypes of breast cancer (BC) and increases with patient age, except triplenegative cancer cases. In reproductive age and perimenopause, the local hormonal environment of breast tumor is characterized by a 1.3- 2.0-fold predominance of androgens over estrogens (p < 0.05), but in postmenopause it depends on the biological subtype of BC. Only in the reproductive period, local hyperandrogenism is associated with the low expression of androgen receptors. As reproductive function fades away, androgen receptor expression increases and, even in perimenopause, relative hyperandrogenism in the tumor is associated with the high level of their expression. Thus, in addition to the standard immunohistochemical panel, it is also necessary to take into account other determinants of tumor biological behavior and menstrual function in women, in particular the local hormonal status of the tumor in combination with the expression of sex hormones, including androgen receptors, which allows consideration of anti-androgen therapy in treating a certain category of patients with BC.